2010
DOI: 10.1016/j.micpath.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Pseudomonas aeruginosa type III cytotoxins is dependent on pseudomonas quinolone signal concentration

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that can, like other bacterial species, exist in antimicrobial resistant sessile biofilms and as free-swimming, planktonic cells. Specific virulence factors are typically associated with each lifestyle and several two-component response regulators have been shown to reciprocally regulate transition between biofilm-associated chronic, and free-swimming acute infections. Quorum sensing (QS) signal molecules belonging to the las and rhl systems are known to regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
1
25
0
2
Order By: Relevance
“…PQS production has been indirectly linked to the regulation of T3S effector secretion in P . aeruginosa at the post-transcriptional level [42]. Interestingly, the rhl QS system that represses both pqsA and pqsR also negatively regulates exoS [43].…”
Section: Resultsmentioning
confidence: 99%
“…PQS production has been indirectly linked to the regulation of T3S effector secretion in P . aeruginosa at the post-transcriptional level [42]. Interestingly, the rhl QS system that represses both pqsA and pqsR also negatively regulates exoS [43].…”
Section: Resultsmentioning
confidence: 99%
“…It appears that exoU is not associated with the risk for VAP but with its severity. Interestingly, the TTSS is negatively controlled by QS [23,24]. Therefore, inhibition of QS by azithromycin should have potentially increased the expression of type III cytotoxins, and therefore the risk for severe VAP.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of the piv gene sequence of strain Pear17 to those of strains possessing the exoU gene rather than the exoS gene, corresponding to increased virulence of this low-protease-containing strain, suggests that the piv gene might be part of a genomic island containing other virulence factors that combine with genome modules within this strain to increase virulence. Singh et al (2010) recently suggested a reciprocal regulation of the TTSS and Pseudomonas Quinolone Signal (PQS), both regulated by the las and rhl quorum-sensing systems (Bleves et al, 2005). Furthermore, host defences can disrupt quorum sensing of invading P. aeruginosa (Chun et al, 2004), suggesting a complex interplay of virulence factors and an orchestration of host and pathogen responses during infection, all of which requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%